„Miasto ogród”. Analiza możliwości wykorzystania walorów urbanistyczno- krajobrazowych w promocji miasta i budowaniu jego marki na przykładzie wybranych miast polskich - Hulicka, Anna (Polityka i Społeczeństwo, 2021)
The main aim of the article was to determine which of the Polish “Garden Cities” used the historical urban system and their names as a brand. For this purpose, author analyzed most of the strategic documents and reports of the “Garden Cities”, ie. Podkowa Lesna, Zabki, Milanowek, Komorow, Puszczykowo, Wroclaw (district Karlowice), Katowice (Giszowiec), Krakow (district Nowa Huta) and Sokolniki (municipality Ozorkow). The research was focused on the online promotion of these cities and conducted by analysis of their websites and Facebook profiles. The results showed that most of the local governments support the concept of “Garden City”. Generally, effective urban policy is implemented in small cities and cities which have preserved their urban layout. This is noticeable in such cities: Podkowa Lesna and Milanowek. However, developments in Katowice are particularly interesting, as the local government aims to change its image of being a “dirty” and “grey” into a green and friendly city. Podkowa Lesna, Milanowek and Katowice have the best chance of becoming a recognised brand.